Social Media Marketing Optimization to Increase MSME Brand Preference: Systematic Literature Review - Laelah Purnamasari; Mohamad Rizan; Karuniana Dianta A. Sebayang; Setyo Ferry Wibowo (Universitas Linggabuana PGRI Sukabumi, 2024)
This research discusses the importance of optimizing social media marketing strategy for Micro, Small, and Medium Enterprises (MSMEs) to increase brand preference and business success. By considering the characteristics of MSMEs such as size, industry, and experience in using social media, this research highlights several implications that can serve as guidelines for MSMEs in developing effective marketing strategies. In the modern business context, social media has become a very important tool in marketing. However, effective use of social media requires a strategy tailored to each business's characteristics and needs. Micro, Small, and Medium Enterprises (MSMEs) are a sector that needs the right strategy to utilize social media to increase brand preference and competitiveness. This study aims to explore the implications of MSME characteristics on the effectiveness of social media marketing strategies. By taking into account the size of the businesses, the industry in which they operate, and their level of experience in using social media, this study provides deep insights into how MSMEs can optimize their use of social media. One important implication is the need to develop a marketing strategy that is tailored to the needs and target audience of MSMEs. Quality content, active interaction with the audience, effective use of advertising, and continuous data analysis are key factors that MSMEs should consider in designing their social media marketing strategy. The results of this study can provide practical guidance for MSMEs in developing more effective marketing strategies and increasing their business success through social media. By understanding the implications of their characteristics, MSMEs can better utilize the full potential of social media to achieve marketing goals and increase brand preference in an increasingly competitive market